Modeling the Electrophysiological Properties of the Infarct Border Zone - Mendonca Costa, Caroline; Plank, Gernot; Rinaldi, Christopher A.; Niederer, Steven A.; Bishop, Martin J. (Frontiers in Physiology, 2018)
Ventricular arrhythmias in patients with myocardial infarction are thought to be associated with structural and electrophysiological remodelling within the infarct border zone. Personalised computational models have been used to investigate the potential role of the infarct border zone in arrhythmogenesis, which still remains incompletely understood. Most recent models have relied on experimental data to assign border zone properties. However, experimental measurements vary significantly resulting in different computational representations of this region. Here, we review experimental data available in the literature to determine the most prominent properties of the infarct border zone. Computational models are then used to investigate the effect of different representations of the border zone on activation and repolarisation properties, which may be associated with ventricular arrhythmias. Experimental data obtained from several animal species and patients with infarct show that border zone properties vary significantly depending on disease’s stage, with the early disease stage dominated by ionic remodelling and the chronic stage by structural remodelling. In addition, our simulations show that ionic remodelling in the border zone leads to large repolarisation gradients in the vicinity of the scar, which may have a significant impact on arrhythmia simulations, while structural remodelling plays a secondary role. We conclude that it is imperative to faithfully represent the properties of regions of infarction within computational models specific to the disease stage under investigation in order to conduct in-silico mechanistic investigations.